Parental Perspectives on the Role of Applied Behavior Analysis (ABA) Therapy in Managing Behaviors of Children with Autism Spectrum Disorder in Gilgit-Baltistan: https://doi.org/10.55966/assaj.2025.4.1.0102 - Muhammad Hadi Haideri*; Mishal Zahid; Moazzam Ali Shigri (`, 2025)
Autism Spectrum Disorder (ASD) presents significant challenges in social interaction, communication, and adaptive behaviors, particularly in resource-limited regions like Gilgit-Baltistan, Pakistan. This study examines parental perspectives on the effectiveness of Applied Behavior Analysis (ABA) therapy in managing behaviors of children with ASD, focusing on social skills, activities of daily living (ADLs), and academic skills. Using a quantitative descriptive design, data were collected from 52 parents through a validated Likert-scale questionnaire (Cronbach’s alpha = 0.804) via convenience sampling. SPSS version 26 was used for analysis, employing descriptive statistics, t-tests, and one-way ANOVA. Results showed moderate improvements (mean scores: 2.11–2.88) across domains. No significant differences were observed based on parents’ age, education, profession, or child’s age. Therapy duration significantly impacted academic skills (F = 3.971, p = 0.025), with frequent sessions yielding better outcomes. A gender-based difference in academic perceptions was noted (t = 26.09, p < 0.001). The findings highlight ABA’s potential, recommending increased session frequency and further research on gender disparities. Key words: Autism, ABA Therapy, Parental Perspectives, Social Skills, Academic Skills